The spontaneous rise of the herd instinct: Agent-based simulation - (:unkn) unknown (My University, 2019)
An agent-based model of an artificial population is used to simulate the rise of the herd instinct. The problem being investigated is the spontaneous rise of the herd instinct in an artificial population, where the population members have no explicit stimuli of such instinct implanted in their original behavior patterns. The simulations are focused on the creation of the herd instinct in the population that originally does not reveal the gregarious behavior.